Rotation. - Staudte, Wolfgang; Esser, Paul; Korb, Irene; Deickert, Karl-Heinz; Krause, Brigitte (Kanopy Streaming, 2014)
The story of an apolitical working-class family that nevertheless gets drawn into collusion with Nazi policies. Rotation was awarded the Golden Leopard at the 1954 Locarno Film Festival and is ranked by film critics as one of Germany's 100 Most Important Films. Rotation portrays a German family and its support for Hitler during the Nazi period. The apolitical mechanic Hans Behnke considers joining the Nazi party to improve his financial standing. When he helps friends print resistance leaflets, however, his son, a member of the Hitler Youth, betrays him and he gets sent to prison. After the war, father and son meet again. Another classic film by Wolfgang Staudte (The murderers are among us), it explores the individual's struggle within a murderous dictatorship. It was censored by Soviet authorities in East Germany because of its pacifist message and the inclusion of footage from Leni Riefenstahl's Olympia (1936).